Manajemen Pelayanan E-Parking di Kawasan Stadion Gajayana Malang - Yopina, Eliana; Sasmito, Cahyo; Rohman, Abd. (Yayasan Lentera Avanya Nagari, 2024)
E-parking is a government program, namely electronic-based parking services. The use of this electronic parking device makes it easier for people to park their vehicles and pay parking fees using the e-parking system. Gajayana Stadium, Malang City, is one of the locations for implementing e-parking by the Malang City Transportation Department. The aim of this research is to find out how the management of e-parking services by the Malang City Transportation Department increases Regional Original Income (PAD). The type of research used is qualitative with a research focus on e-parking service management, namely by paying attention to the management functions of planning, organizing, implementing and supervising. Snowball sampling is a way for researchers to determine research informants. The research results show that e-parking planning is based on Law No. 28 of 2009 concerning Regional Taxes and Regional Retributions, Malang City Regional Regulation No. 2 of 2011 concerning Business Services Retributions, Malang City Regional Regulation No. 4 of 2009 concerning Parking Lot Management. The organization is in accordance with the provisions where there are officers according to their respective functions, the implementation of e-parking is running effectively with the increase in Malang City PAD in the parking sector, and supervision is also carried out regularly so as to maximize control in e-parking services.